Mayo Registry for Telemetry Efficacy in Arrest Study: An Assessment of the Utility of Telemetry in Predicting Clinical Decompensation. (March 2018) - Snipelisky, David; Ray, Jordan; Matcha, Gautam; Roy, Archana; Harris, Dana; Bosworth, Veronica; Dumitrascu, Adrian; Clark, Brooke; Vadeboncoeur, Tyler; Kusumoto, Fred; Bowman, Cammi; Burton, M. Caroline
Introduction: Our study assesses the utility of telemetry in identifying decompensation in patients with documented cardiopulmonary arrest. Methods: A retrospective review of inpatients who experienced a cardiopulmonary arrest from May 1, 2008, until June 30, 2014, was performed. Telemetry records 24 hours prior to and immediately preceding cardiopulmonary arrest were reviewed. Patient subanalyses based on clinical demographics were made as well as analyses of survival comparing patients with identifiable rhythm changes in telemetry to those without. Results: Of 242 patients included in the study, 75 (31.0%) and 110 (45.5%) experienced telemetry changes at the 24-hour and immediately preceding time periods, respectively. Of the telemetry changes, the majority were classified as nonmalignant (n = 50, 66.7% and n = 66, 55.5% at 24 hours prior and immediately preceding, respectively). There was no difference in telemetry changes between intensive care unit (ICU) and non-ICU patients and among patients stratified according to the American Heart Association telemetry indications. There was no difference in survival when comparing patients with telemetry changes immediately preceding and at 24 hours prior to an event (n = 30, 27.3% and n = 15, 20.0%) to those without telemetry changes during the same periods (n = 27, 20.5% and n = 42, 25.2%; P = .22 and .39). Conclusion: Telemetry has limited utility in predicting clinical decompensation in the inpatient setting.